La interminable lucha por la protección de los derechos humanos en Myanmar (2013)
This document presents an analysis of one of the crises that occurs in Myanmar due to the constant violation of international law and human rights. This paper is made from the point of view of international law and international organizations that have analyzed the conflict, studying the origins of the conflict from history, its current landscape and the positions taken by the international community and the Burmese State.